Akuntabilitas dan Transparansi Pelaporan Kegiatan dan Laporan Keuangan di Perkumpulan Ruang Belajar Aqil - Nurhuda; Prima Yusi Sari (P3M Politeknik Negeri Bengkalis, 2025)
This study analyzes accountability and transparency in the activity reporting and financial statements of Perkumpulan Ruang Belajar Aqil, a non-profit organization in Malang City, with the aim of determining whether the reporting meets good principles of accountability and transparency. The research method used is descriptive qualitative with a combined data collection technique (triangulation) through observation, interviews, and documentation. Data analysis includes data reduction, data presentation, and conclusion. The results indicate that Perkumpulan Ruang Belajar Aqil has effectively implemented the principles of accountability and transparency, as reflected in systematic documentation in the Buku Induk, RBA Annual Report, and Financial Statements. To enhance accountability, it is recommended that the organization focus more on the details outlined in the ISAK 35 standard and use accounting software to ensure the security and accuracy of financial reports. Transparency is demonstrated through the dissemination of information on the website and social media. It is also recommended to broaden the information reach by posting accountability reports on bulletin boards and providing physical suggestion boxes and digital platforms. These findings provide insights into improving accountability and transparency in non-profit organizations and offer a model that can be adopted by similar organizations.